The growth performance and survival rate of catfish (Clarias sp.) that given probiotic controlling nitrogen. Issue 1 (June 2020) - Yosmaniar,; Pantjara, B; Setiadi, E
Abstract: The water quality can be improved by using probiotics as bioremediation. The probiotics are a consortium of nitrification and denitrification bacteria ( Pseudomonas aeruginosa and Achromobacter insuavis ), which both of the indigenous bacteria are the products of the Research Institute for Freshwater Aquaculture and Fisheries Extension (RIFA). The objective study is to determine the adding frequency of RIFA probiotic into the water fish pond of catfish culture concerning growth performance and survival. The catfish fingerling with a size of 7-8 cm long and weighing 16.45 ± 0.3 g was used. The stocking density was 750 fish/pond. Nine plastic sheet ponds with a water volume of 1.6 m 3 and completed with aeration were used. A dose of probiotics was 10 mL/m 3 . The difference in adding the frequency of probiotic as a treatment was as followed: A) every 5 days; B) every 10 days, and C) without probiotics. The parameters measured survival rate (SR), absolute weight growth, specific growth rate (SGR), feed conversion ratio (FCR), water quality. One way ANOVA with three treatments and three replications were performed. The results showed that the use of probiotics could control nitrogen compounds in catfish cultivation, where the frequency of administration every 5 days gives the best results.